Liderazgo docente en el proceso de enseñanza aprendizaje en la Unidad Educativa “Vicente León” en el año lectivo 2016-2017. - Molina Falconí, Martha Isabel (2017)
The purpose of the research was to determine the influence of the teaching leadership in the teaching process at "Vicente León" Educational Unit, in order to analyze it beyond the established positions and destined to the business organizations, extending it to the educational field and thus actively stimulate it among all the members of the Institution, since its absence or scarcity generates stagnation. The development of the research was based on the necessary bibliographical material to elaborate the theoretical framework, for which the field work was carried out at Educational Unit "Vicente León", of the city of Latacunga province of Cotopaxi; through the application of the surveys carried out to the participants: teachers and students, it was possible to obtain the results and information necessary to this problem. It was concluded that teaching leadership affects the learning process of learners; here is the importance of developing leadership in the teacher, being an essential aspect in all its development. It allows work based on creativity, motivation and trust; essential characteristics that they incur in all academic and personal activity. It was finalized by establishing the conclusions of the research carried out, accompanied by its due recommendations.